2022
DOI: 10.3390/agriculture12030374
|View full text |Cite
|
Sign up to set email alerts
|

Germination and the Biochemical Response of Pumpkin Seeds to Different Concentrations of Humic Acid under Cadmium Stress

Abstract: The poisoning of heavy metals and their accumulation in food chains are major environmental and health risks. There have been several reports that determined that pumpkins tend to collect small amounts of nitrate or heavy metals. Therefore, the aim of the present study is to investigate the effect of organic matter (humic acid) on the germination and activity of antioxidant enzymes, glycosylate cycle enzymes, and utilization of lipid and protein reserves of pumpkin seeds under cadmium stress conditions. An exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 57 publications
1
6
0
Order By: Relevance
“…Our findings reveal that even at low concentrations (100 µM) of cadmium or copper, the lengths and weights of zucchini seedlings experience a significant reduction compared to the control (Table 1 ). As supported by Asadi Aghbolaghi, et al 23 , higher concentrations of cadmium (200 mg/L) can lead to the decline of protein and lipid structures due to the influence of free radicals, resulting in a reduction of these reserves. Additionally, previous studies have shown that oxidative stress induced by osmotic stress 50 and the involvement of reactive oxygen species (ROS) play a role in programmed cell death during germination and seedling development.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Our findings reveal that even at low concentrations (100 µM) of cadmium or copper, the lengths and weights of zucchini seedlings experience a significant reduction compared to the control (Table 1 ). As supported by Asadi Aghbolaghi, et al 23 , higher concentrations of cadmium (200 mg/L) can lead to the decline of protein and lipid structures due to the influence of free radicals, resulting in a reduction of these reserves. Additionally, previous studies have shown that oxidative stress induced by osmotic stress 50 and the involvement of reactive oxygen species (ROS) play a role in programmed cell death during germination and seedling development.…”
Section: Discussionmentioning
confidence: 90%
“…The phytotoxic effects of cadmium (Cd) and copper (Cu) on seed germination and seedling development have been documented by various researchers in different plant species, including zucchini ( C. pepo ) 57 , Atriplex ( A. halimus ) 59 , mung bean ( P. aureus Roxb) 60 , and rice ( O. sativa ) 61 . Recent research by Asadi Aghbolaghi, et al 23 concluded that C. pepo seeds exhibit relative tolerance to the toxic effects of cadmium at an early stage of germination, accompanied by a depletion in protein and lipid reserves, as well as a reduction in seed vigor and the activity of antioxidant enzymes such as catalase (CAT), superoxide dismutase (SOD), and peroxidase (POX) in germinated zucchini seeds.…”
Section: Discussionmentioning
confidence: 99%
“…Variations in seed oil affect membrane lipid composition in terms of function and membrane permeability, which affects germination, establishment, and tolerance to environmental stresses [37]. In oilseeds, the first step of food storage consumption is performed by the lipase enzyme, which breaks ester bonds and releases fatty acids and glycerol due to the activity of this enzyme [38,39].…”
Section: Discussionmentioning
confidence: 99%
“…However, there is much variation in the chemical composition of humic substances, in addition to different effects depending on the crop species (Asadi Aghbolaghi et al, 2022;Rostami et al, 2022, Sensoy et al, 2022. Therefore, it is necessary to evaluate the application of humic substances in short-term cycle fruit species growing under the conditions of the Brazilian Cerrado.…”
Section: Introductionmentioning
confidence: 99%